A comparative study of replicative properties of antitumor recombinant vaccinia viruses on human glioblastoma cell culture U87 and monkey kidney cell culture CV-1 - R. A. Maksyutov; I. V. Kolosova; T. V. Tregubchak; I. A. Razumov; S. N. Shchelkunov (Вавиловский журнал генетики и селекции)
In the world of today, virotherapy is one of the rapidly developing areas in the treatment of cancer, and its advantage is selective destruction of cancer cells with minimizing the destructive effect on normal cells of the body. A promising basis for the creation of oncolytic drugs is orthopoxviruses, which have a number of advantages over other viral vectors, and one of these advantages is a large capacity of the genome, which allows genes encoding proteins with antitumor properties to be cloned into their genome. In this study, we compared the replicative properties of ten variants of vaccinia virus (the strain LIVP of VACV) using human glioblastoma cell culture; some of these viruses have additional genes, such as the gene encoding granulocyte-macrophage colony stimulating factor, gene encoding apoptosis-inducing protein TRAIL and gene encoding green fluorescent protein. Furthermore, the virus with five virulence genes deleted (genes encoding hemagglutinin, γ-interferonbinding protein, thymidine kinase, complementbinding protein and Bcl2-like inhibitor of apoptosis), which has significantly lower reactogenicity and neurovirulence compared to the original strain LIVP of VACV, was studied. These data suggest that variants of vaccinia virus with a defective gene encoding thymidine kinase most actively replicate in glioblastoma cell culture.